(untitled) (Research, Society and Development, 2022)
The central giant cell lesion of the maxillary is a rare intraosseous lesion, which presents a variable clinical and radiographic behavior. Its conventional treatment consists of surgical removal, however there are several associated factors, such as the patient’s age, extension and behavior of the lesion that are taken. into account in choosing the appropriate treatment. The aim of the study is to report a clinical case of LCCG in the posterior region of the mandible, in a 35-year-old female patient, complaining of hardened increase in volume and tooth mobility of the elements close to the lesion, where an intralesional injection of 8mg of corticosteroids was do per weekly, fortnightly and monthly sessions for 6 months, after that, enucleation with curettage and total removal of the lesion, and extraction of elements affected and compromised by caries and periodontal lesions were performed. Central giant cell lesion requires a precise diagnosis, in order to select the appropriate treatment, taking into account the characteristics of the lesion in each patient. In aggressive lesions, the treatment is always surgical due to the higher success rate.